Knowledge, atttitude and practice of agro based food processing technology among small medium entrepreneurs - Azman, Norsyahirah (2014)
Agro based industry in Malaysia are one important component in Agriculture development. The aim of this program is to increase entrepreneur’s income and produce more processed food from various raw materials from crop, animal and fish. Most developing countries recognize the importance of the small and medium scale enterprise (SME) sector for economic development. However, the establishment and successful operation of small scale food processing enterprises also have face several constraints and we do not know how far they can solve the problem related. This study is to identify acceptance of agro based food processing technology adoption among Small and Medium Enterprises (SME) entrepreneurs. This study focusing on Selangor and Johor to provide answers to some questions related to knowledge, attitude, practice and skills of agro based food processing technology among small medium entrepreneurs. 110 respondents consisted of entrepreneurs were randomly selected in this project. One set of questionnaire was given to each of the respondents to fill in their personal profile, company profile and other important part which related to this study. All the collected data were in the raw form and statistical analysis with SPSS version 21.0 software was carried out to analyze these data. From the result, Chips are the highest percentage of product produce by the respondents and mixture technology is the highest percentage which is the basic technology of food processing. Most of the respondents get the knowledge of food processing technology from the agricultural agencies Respondents have high level of knowledge, attitude, practice and skill of food processing technology based on the mean level of the study. The acceptance level of food processing technology is high. So, we can conclude that food processing technologies have given positive impact to the small medium agro based food processing. Net incomes have significant relationship with the level of knowledge of food processing technology. The result same goes to the level of attitude of food processing technology. Gender has relationship with the level of practice of food processing technology. Marital status has significant relationship with the level of skill of food processing technology.